Intensitas menonton tayangan kekerasan di media sosial internet dengan perilaku agresif anak sekolah di SD Negeri 1 Tirtomoyo - Puspitasari, Candra Dewi, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
Elementary school age children have known internet usage but not yet aware of its negative impact. Impressions of violence in video games can affect the behavior of suspected online through imitate a scene of violence. Quarrel with friends in schools supposedly one of them because the children tried to replicate a character the game they love. This research aims to know the relationship of the intensity of watching violence on the internet social media with aggressive behavior in elementary school children SD Negeri 1 Tirtomoyo. This research is descriptive research of correlative with the approach of cross sectional. The population of the research was the child who goes to school in SD Negeri 1 Tirtomoyo which consist of class 1 to class 6 with a total of 117 children and who can already surf the internet as well as online gaming as much as 87. As many as 87 research sample school child who already can playing the internet and online gaming with the total sampling techniques. Data collection using a questionnaire and analyzed using Chi Square test. The research results obtained 2count of 4.979 (p-value = 0.026), cross-tabulations based on then there is a significant relationship between the intensity of watching violence on the internet social media with aggressive behavior in elementary school children SD Negeri 1 Tirtomoyo. Conclusion the higher intensity of watching violence in social media internet then aggressive behavior in children getting high. Keywords: School children, violent impressions, aggressive behavior